PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN PUBLIK DAN PENERAPAN INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) TERHADAP AUDIT REPORT LAG - Carania Metta; Effriyanti Effriyanti (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2020)
This study aims to find out and obtain evidence about Company Size, Public Ownership and Application of International Financial Reporting Standards (IFRS) to Lag Audit Reports. This type of research is quantitative research with descriptive research. The population in this study was LQ-45 companies listed on the Indonesia Stock Exchange in 2010-2018 which were bought by 95 companies. The sampling technique used a purposive sampling method. With a total of 81 research data. Hypothesis testing in this study uses linear multiple regression. Firm size and International Financial Reporting Standards (IFRS) do not affect the audit lag report, while public ownership is related to the audit lag report